2023
DOI: 10.3390/jcm12165173
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothetical New Challenging Use for Indocyanine Green Fluorescence during Laparoscopic Appendectomy: A Mini-Series of Our Experience and Literary Review

Abstract: Laparoscopic appendectomy (LA) is a well-standardized surgical procedure, but there are still controversies about the different devices to be used for the appendiceal stump closure and the related postoperative complications. Indocyanine green (ICG) fluorescence angiography (FA) has already been shown to be helpful in elective and emergency surgery, providing intraoperative information on tissue and organ perfusion, thus guiding the surgical decisions and the technical strategies. According to these two aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…ICG FA has also been used to assess the base of the appendix before appendectomy. Zorzetti et al reported five cases where ICG was used to assess the base of the appendix prior to appendectomy and the perfusion of the stump after completion of the appendectomy ( 93 ).…”
Section: Colon Surgerymentioning
confidence: 99%
“…ICG FA has also been used to assess the base of the appendix before appendectomy. Zorzetti et al reported five cases where ICG was used to assess the base of the appendix prior to appendectomy and the perfusion of the stump after completion of the appendectomy ( 93 ).…”
Section: Colon Surgerymentioning
confidence: 99%